Project-based second and foreign language education : past, present, and future - Beckett, Gulbahar H., 1959-; Miller, Paul Chamness (Emerald Publishing Limited : Information Age Pub., 2006)
Dewey's idea of Project-based Learning (PBL) was introduced into the field of second language education nearly two decades ago as a way to reflect the principles of student-centered teaching (Hedge, 1993). Since then, PBL has also become a popular language and literacy activity at various levels and in various contexts (see Beckett, 1999; Fried-Booth, 2002; Levis & Levis, 2003; Kobayashi, 2003; Luongo- Orlando, 2001; Mohan & Beckett, 2003; Weinstein, 2004). For example, it has been applied to teach various ESL and EFL skills around the world (e.g., Fried-Booth, 2002). More recently, PBL has been heralded as the most appropriate approach to teaching content-based second language education (Bunch, et al., 2001; Stoller, 1997), English for specific purposes (Fried-Booth, 2002), community-based language socialization (Weinstien, 2004), and critical and higher order thinking as well as problem-solving skills urged by the National Research Council (1999). Despite this emphasis, there is a severe shortage of empirical research on PBL and research-based frameworks and models based on sound theoretical guidance in general and second and foreign language education in particular (Thomas, 2000). Also missing from the second and foreign language education literature is systematic discussion of PBL work that brings together representative work, identifying obvious gaps, and guiding the field toward future directions. This, first of its kind, volume bridges these obvious gaps through the original work of international scholars from Canada, Israel, Japan, Singapore, and the US.
Keywords: Language and languages -- Study and teaching.; Project method in teaching.; Education -- Teaching -- Methods & Strategies.; Project-based learning.; Teaching skills and techniques.; elektronické knihy; electronic books